Intellectual development of children born to mothers with epilepsy - A. V. Yakunina (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2017)
Objective: to investigate the level of intellectual development in children born to mothers with epilepsy.Patients and methods. The Wechsler test was used to examine 30 epileptic mother–child pairs (a study group) and 10 healthy mother–child ones (a control group). The children’s mean age was 8 years 9 months in the study group and 7 years 8 months in the control group.Results. In the children from the study group, the general, verbal and non-verbal intelligence quotient (IQ) scores were 126.6, 112.3, and 136.2, respectively. There were no statistically significant differences in IQ scores between the two groups of children. The comparison of the IQ scores in children who did not take antiepileptic drugs and those who received valproic acid and carbamazepine showed no statistical differences. The IQ was comparable or higher in the children than that in their mothers with epilepsy.Conclusion. The IQ scores in the children born to epileptic mothers are moderate and higher and do not differ from those in the children born to healthy mothers.